2011
DOI: 10.3399/bjgp11x572427
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of symptoms for colorectal cancer in primary care: a systematic review

Abstract: BackgroundOver 37 000 new colorectal cancers are diagnosed in the UK each year. Most present symptomatically to primary care. AimTo conduct a systematic review of the diagnostic value of symptoms associated with colorectal cancer. DesignSystematic review. MethodMEDLINE, Embase, Cochrane Library, and CINAHL were searched to February 2010, for diagnostic studies of symptomatic adult patients in primary care. Studies of asymptomatic patients, screening, referred populations, or patients with colorectal cancer rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(203 citation statements)
references
References 29 publications
8
179
1
6
Order By: Relevance
“…7 A specific level of PPV prompting referral cannot be established, but studies indicate that levels above 1% should prompt investigation. 4,7 As in the study by Scheel et al, 9 6.2% (279 of 4518) of the patients in the current study were diagnosed with a serious disease without the GP having a suspicion of one being present after the index consultation.…”
Section: Provenancementioning
confidence: 63%
See 1 more Smart Citation
“…7 A specific level of PPV prompting referral cannot be established, but studies indicate that levels above 1% should prompt investigation. 4,7 As in the study by Scheel et al, 9 6.2% (279 of 4518) of the patients in the current study were diagnosed with a serious disease without the GP having a suspicion of one being present after the index consultation.…”
Section: Provenancementioning
confidence: 63%
“…1 When patients present with symptoms and signs in general practice, the positive predictive values (PPVs) of serious disease are low (often <5%), whereas the frequency of 'low-risk-but-not-no-risk' symptoms and signs is high. [2][3][4][5][6][7] This fundamental conflict constitutes a major clinical challenge for GPs and for the organisation of the entire healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…The authors clearly stated that the physicians should continue to rely on the clinical findings for detecting this cancer. Studies have reported the presence of rectal bleeding as a single symptom or it may also present in conjunction with other symptoms (Astin et al, 2011). Most of the symptoms present more rampantly in higher stage tumors as an indicator of the aggressive nature of this disease, however, this may not always be true.…”
Section: Discussioncmentioning
confidence: 99%
“…Exophytic tumors are most often located in the right half of the colon, while stenosing tumors are mostly found in its left half. The majority (up to 75%) of colorectal cancer occur within the descending colon, sigmoid colon and rectum, 15% of cases are located in the cecum and ascending colon, and only 10% in the transverse colon (13,14,15). Adenocarcinoma accounts for more than 95% of colorectal cancer cases.…”
Section: Pathologymentioning
confidence: 99%